ELECTROLUMINESCENCE STUDY OF InP/InGaAsP/InAs/InP P-I-N LASER HETEROSTRUCTURE - Bozkurt, Kutsal (YILDIZ TECHNICAL UNIV, 2016)
MBE (Molecular Beam Epitaxy) grown p-i-n laser heterostructure, based on InAs/InP Quantum Dashes with quaternary InGaAsP Quantum Well, were investigated through electroluminescence (EL) measurements. Bipolar injection set on just of forward bias, V-F, 1.3 V, resulting an emission of long wavelength laser light, peaking of 1550 nm. This value was consistent with thermal energy band gap, deduced from current-voltage measurement in space charge limited regime where mobility of injected carriers followed Poole-Frenkel type conduction.
Keywords: EL; quantum dashes; annihilation; Engineering